Profiling Junior High School Students’ Spatial Ability in Geometry Transformations Based on Five Spatial Indicators - Fitriyana, Nur; Luthfiana, Maria; Purwasi, Lucy Asri (Mimbar Sekolah Dasar, 2025)
Spatial ability plays an essential role in students’ cognitive development, particularly in learning mathematics and science. This study aims to map the initial profile of junior high school students’ visual–spatial ability by emphasizing five cognitive indicators: spatial perception, spatial visualization, mental rotation, spatial relations, and spatial orientation. The research employed a mixed-methods approach, combining a quantitative descriptive design with qualitative data from interviews. The quantitative instrument consisted of five validated essay test items with acceptable reliability (α = 0.78). The research subjects were 23 ninth-grade students from a junior high school in Rejang Lebong Regency, Bengkulu. The analysis revealed that 43.48% of students were in the low category, 47.83% in the medium category, and only 8.69% reached the high category. The highest achievement was found in the spatial perception indicator (91.30%), while the lowest was in mental rotation (34.78%). Interview data supported the quantitative findings, showing that students still experienced difficulties in mentally manipulating objects. These findings highlight the importance of spatial skills in supporting the understanding of geometric concepts and indicate the need for instructional strategies that place greater emphasis on visualization and rotation aspects. This study is expected to serve as a foundation for developing effective, adaptive, and contextual spatial-based mathematics learning.